Solid-State Silver-Catalyzed Ring-Opening Fluorination of Cyclobutanols by Using Mechanochemistry - Isshiki, Ryota; Kubota, Koji; Ito, Hajime (Synlett, 2023)
In this report, we demonstrate that a ball-milling technique facilitates fast and efficient silver-catalyzed ring-opening fluorination of cyclobutanols. This is the first report of a catalytic C–C bond-cleavage/functionalization reaction under solid-state mechanochemical conditions. The developed protocol affords a high yield of γ-fluorinated ketones within much shorter reaction times, and requires less silver catalyst and Selectfluor compared with the previous solution-based conditions. Notably, the process can be carried out in air. Because of the reduced use of chemicals and the simple time-saving experimental procedures, this technique is an efficient and environmentally friendly way to access γ-fluorinated ketones.
Keywords: C–C bond cleavage; fluorination; mechanochemistry; ball-milling; solid-state chemistry; silver catalysis